Psychometric properties of the scale on the knowledge and pedagogical practice of teachers towards students with ADHD - Sandra Milena Carrillo Sierra; Gloria Silva Monsalve; Claudia Carolina Cabrera Gómez; Carlos Gutiérrez Suárez; Nayareth Rincón Rodriguez; Diego Rivera Porras (Revista Criterios, 2023)
The psychometric properties of the scale of knowledge and pedagogical practice of teachers against inattention, hyperactivity and impulsivity behaviors in school contexts in Cúcuta, Norte de Santander are validated. It was carried out under a quantitative, non-experimental approach, of the exploratory, cross-sectional type, in terms of the population to be taken into account, they were the teachers assigned to the municipal education secretary, in relation to the sample, it was obtained by proportional fixing; the data will be processed in SPSS applying exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) based on reliability and reproducibility Cronbach's alpha, test-retest with Lin's intraclass correlation coefficient and the kappa index Cohen's. It is concluded that the test has the pertinent psychometric properties for use in Colombian school contexts.